Effect of Anatomic Segment Involvement on Stereotactic Radiosurgery for Facial Nerve Schwannomas: An International Multicenter Cohort Study - Mehta, Gautam U; Lekovic, Gregory P; Slattery, William H; Brackmann, Derald E; Long, Hao; Kano, Hideyuki; Kondziolka, Douglas; Mureb, Monica; Bernstein, Kenneth; Langlois, Anne-Marie; Mathieu, David; Nabeel, Ahmed M; et al. (Neurosurgery, 2020)
BACKGROUND: Facial nerve schwannomas are rare, challenging tumors to manage due to their nerve of origin. Functional outcomes after stereotactic radiosurgery (SRS) are incompletely defined. OBJECTIVE: To analyze the effect of facial nerve segment involvement on functional outcome for these tumors. METHODS: Patients who underwent single-session SRS for facial nerve schwannomas with at least 3 mo follow-up at 11 participating centers were included. Preoperative and treatment variables were recorded. Outcome measures included radiological tumor response and neurological function. RESULTS: A total of 63 patients (34 females) were included in the present study. In total, 75% had preoperative facial weakness. Mean tumor volume and margin dose were 2.0 ± 2.4 cm3 and 12.2 ± 0.54 Gy, respectively. Mean radiological follow-up was 45.5 ± 38.9 mo. Progression-free survival at 2, 5, and 10 yr was 98.1%, 87.2%, and 87.2%, respectively. The cumulative proportion of patients with regressing tumors at 2, 5, and 10 yr was 43.1%, 63.6%, and 63.6%, respectively. The number of involved facial nerve segments significantly predicted tumor progression (P = .04). Facial nerve function was stable or improved in 57 patients (90%). Patients with involvement of the labyrinthine segment of the facial nerve were significantly more likely to have an improvement in facial nerve function after SRS (P = .03). Hearing worsened in at least 6% of patients. Otherwise, adverse radiation effects included facial twitching (3 patients), facial numbness (2 patients), and dizziness (2 patients). CONCLUSION: SRS for facial nerve schwannomas is effective and spares facial nerve function in most patients. Some patients may have functional improvement after treatment, particularly if the labyrinthine segment is involved.
Keywords: nervus facialis; Labyrinthine; nádory kraniálních nervů; Humans; nemoci lícního nervu; lidé středního věku; dítě; Cranial Nerve Neoplasms; kohortové studie; Child; Female; Aged; mladý dospělý; dospělí; výsledek terapie; senioři; lidé; Schwannoma; Stereotactic radiosurgery; Cohort Studies; radiochirurgie; Adult; neurilemom; Facial Nerve; Radiosurgery; Facial nerve; ženské pohlaví; Radiation; Male; Facial Nerve Diseases; Middle Aged; Retrospective Studies; Adolescent; Treatment Outcome; Young Adult; retrospektivní studie; Neurilemmoma; mužské pohlaví; mladiství